Characterisation of soluble microbial products (SMPs) in anaerobic bioreactors - Le, Chencheng (2018)
The primary aim of this research was to develop a variety of methods for the specific characterisation of soluble microbial products (SMPs) that are produced during substrate metabolism or cell lysis and degradation in anaerobic treatment. In biological wastewater treatment processes, the analysis of metabolic compounds that are produced during the process is critical to monitoring the performance of system; these soluble products directly affect process efficiency (removal of oxidizable compounds) and quality of the effluent after treatment, and are also one of the major causes of fouling in membrane bioreactors. However, analysing them is challenging due to their inherently dilute nature (sub ppm level) and heterogeneity. In this PhD project, the chemical composition of SMPs produced during the anaerobic condition will be identified and quantified using both sophisticated analytical instruments, e.g. GC-MS, and conventional chemical analyses. Firstly, an analytical methodology for low molecular weight SMPs (<580 Da) in wastewater treatment systems was established using a combination of solid phase extraction (SPE) and liquid-liquid extraction (LLE), which was optimized and enabled the maximum number of compounds to be identified. Next, conventional colorimetric measurements of carbohydrates and proteinaceous materials generated from anaerobic bioreactor were critically evaluated. These result highlighted the severe limitations of these dated assays, and the need for exercising care when interpreting results, particularly where complex heterogeneous wastewater is concerned. Then protocols for the characterisation of free amino acids using HPLC, and for elucidating the monomeric structure of loosely bound exopolysaccharides (EPS) using GC-MS were developed in order to gain greater insights into the biological transformations occurring in anaerobic digestion (AD), and the SMPs produced. Finally, all these optimized methods were employed to comprehensively assess the impact of different carbohydrate substrates (glucose, fructose and sucrose) and nitrogen sources (urea and NH4Cl) on the production and composition of SMPs during AD. This study revealed that these macronutrients could strongly influenced many measures of wastewater quality, and the results clearly demonstrated that well-characterized nutritional conditions ensure a cooperative bacterial symbiosis converting complex organic matter to biogas effectively. All the findings in this project provide fresh and useful insights into an area that is under researched, and often overlooked by engineers studying overall engineered wastewater treatment systems.